Редукція і геометричне квантування - Микитюк, І.В.; Прикарпатський, А.К. (Український математичний журнал, 1992)
Построена конструкция, которая позволяет по процедуре геометрического квантования, реализованной для гамильтоновой системы с симметриями, геометрически проквантовать редуцированную гамильтонову систему (найти дискретный спектр и соответственные собственные функции, если таковы найдены для исходной системы). Эта конструкция применена для геометрического квантования системы, полученной редукцией гамильтоновой системы, определяемой геодезическим потоком на n-мерной сфере. A construction is created that makes it possible to geometrically quantize a reduced Hamiltonian system using the procedure of geometric quantization realized for a Hamiltonian system with symmetries (i.e., to find the discrete spectrum and the corresponding eigenfunctions, if these have been found for the initial system). The construction is used to geometrically quantize a system obtained by reduction of a Hamiltonian system that determines the geodesic flow on an n-dimensional sphere.